Makna Akuntabilitas bagi Para Pimpinan di Pemerintahan: Studi Kasus Satuan Polisi Pamong Praja Kota Padang - Rajaskana, Ade; Deviani, Deviani (Jurnal Nuansa Karya Akuntansi, 2025)
This study aims to determine the meaning of accountability for the leaders of the Padang City Civil Service Police Unit. This study is a qualitative approach study using a phenomenological research type. This study observes and listens more carefully and in detail to the explanation and understanding of individuals towards their experiences and explores the meaning through exploring the experiences of the subjects being studied. The researchers in this study collected data through interviews with the leaders of the Padang City Civil Service Police Unit. The results of the study stated that the leaders of the Civil Service Police Unit had understood the meaning of accountability which was seen in terms of aporia, testimony, and gift, but after further study the leaders interpreted accountability more in terms of aporia. Research on the meaning of accountability for leaders is still very little. And the researcher conducted the research in the Padang City area, where in this area the research conducted by the researcher is something new. This study has a contribution, namely based on the results of the study, it can pay attention to how the understanding of accountability and its implementation for the leaders of an organization and can be an inspiration for anyone to conduct similar research.